Consensus on a Multidisciplinary Treatment Guideline for de Quervain Disease: Results From the European HANDGUIDE Study. Issue 8 (1st August 2014) - Huisstede, Bionka M.A.; Coert, J. Henk; Fridén, Jan; Hoogvliet, Peter; ,
Abstract : Background: De Quervain disease is a common pathology resulting in pain caused by resisted gliding of the abductor pollicis longus and extensor pollicis brevis tendons in the fibro-osseous canal. In a situation of wavering assumptions and expanding medical knowledge, a treatment guideline is useful because it can aid in implementation of best practices, the education of health care professionals, and the identification of gaps in existing knowledge. Objective: The aim of this study was to achieve consensus on a multidisciplinary treatment guideline for de Quervain disease. Design: A Delphi consensus strategy was used. Methods: A European Delphi consensus strategy was initiated. A systematic review reporting on the effectiveness of surgical and nonsurgical interventions was conducted and published and was used as an evidence-based starting point for this study. In total, 35 experts (hand therapists and hand surgeons selected by the national member associations of their European federations and physical medicine and rehabilitation physicians) participated in the Delphi consensus strategy. Each Delphi round consisted of a questionnaire, an analysis, and a feedback report. Results: Consensus was achieved on the description, symptoms, and diagnosis of de Quervain disease. The experts agreed that patients with this disorder should always receive instructions and that these instructions should be combined with another form of treatment and should not be used as a sole treatment. Instructions combined with nonsteroidal anti-inflammatory drugs (NSAIDs), splinting, NSAIDs plus splinting, corticosteroid injection, corticosteroid injections plus splinting, or surgery were considered suitable treatment options. Details on the use of instructions, NSAIDs, splinting, corticosteroid injections, and surgery were described. Main factors for selecting one of these treatment options (ie, severity and duration of the disorder, previous treatments given) were identified. A relationship between the severity and duration of the disorder and the choice of therapy was indicated by the experts and reported in the guideline. Limitations: One of the limitations of a Delphi method is its inability to forecast future developments. It investigated current opinions of the treatment of people with de Quervain disease. Conclusions: This multidisciplinary treatment guideline may help in the treatment of and research on de Quervain disease.